Democratic School Culture and Student–Teacher Relationships: Insights from Native and Immigrant-Background Students - Igor Peras; Simona Bezjak (Social Sciences, 2025)
This paper examines how various dimensions of democratic school and classroom culture—openness in classroom discussions, peer interactions, civic learning, influence on decision-making, and civic participation—relate to perceptions of student–teacher relationships of two distinct groups of students (native and immigrant-background students) in Slovenia. Using representative data from the International Civic and Citizenship Education Study (ICCS 2022 cycle), analyses revealed that student-perceived positive peer interactions and decision-making influence were consistent, strong predictors of positive student–teacher relationships for both groups of students. However, open classroom discussions and civic learning at school were only significant for native students, suggesting that these aspects of classroom life may not resonate uniformly with all students. Moreover, participation in civic activities, although often seen as an integral part of democratic school culture, emerged as a significant negative predictor of student–teacher relationships only among students with an immigrant background, indicating that these activities may inadvertently highlight barriers or differences rather than promote inclusive engagement. Results are discussed through the lens of fostering positive student–teacher relationships for all students.